2023
DOI: 10.3390/antiox12030663
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Flavonoids and Flavonoid Metabolites in the Treatment of Neurodegenerative Pathology in Disorders of Cognitive Decline

Abstract: Flavonoids are a biodiverse family of dietary compounds that have antioxidant, anti-inflammatory, antiviral, and antibacterial cell protective profiles. They have received considerable attention as potential therapeutic agents in biomedicine and have been widely used in traditional complimentary medicine for generations. Such complimentary medical herbal formulations are extremely complex mixtures of many pharmacologically active compounds that provide a therapeutic outcome through a network pharmacological ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 423 publications
1
11
0
Order By: Relevance
“…[20] Flavonoids, being the most abundantly occurring and extensively studied among the polyphenols, demonstrate considerable potential in treating NAFLD due to their inherent safety, widespread availability, and diverse biological activities. [21–23] The flavonoids identified in this study, namely, quercetin, kaempferol, and naringenin, offer promising advantages in NAFLD treatment through various mechanisms, which is consistent with findings from other studies. [24] Many in vivo and in vitro experimental evidence have identified various molecular mechanisms of quercetin in preventing the occurrence and progress of NAFLD, including antioxidant stress, anti-inflammatory, improving fatty acid metabolism, and regulating gut microbiota and bile acid metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…[20] Flavonoids, being the most abundantly occurring and extensively studied among the polyphenols, demonstrate considerable potential in treating NAFLD due to their inherent safety, widespread availability, and diverse biological activities. [21–23] The flavonoids identified in this study, namely, quercetin, kaempferol, and naringenin, offer promising advantages in NAFLD treatment through various mechanisms, which is consistent with findings from other studies. [24] Many in vivo and in vitro experimental evidence have identified various molecular mechanisms of quercetin in preventing the occurrence and progress of NAFLD, including antioxidant stress, anti-inflammatory, improving fatty acid metabolism, and regulating gut microbiota and bile acid metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…51 Alternatively, it was reported that the gut microbiota generates bioactive flavonoid metabolites, retaining anti-oxidative and anti-inflammatory properties, which could stimulate vagus nerve signals or be transported to the brain via systemic circulation, processes that are important for treating neurological disorders. 52 In the case of the application of Seabuckthorn, the intake of Seabuckthorn polysaccharide in high-fat diet-induced mice with cognitive dysfunctions reversed gut dysbiosis by correcting the reduction of Ileibacterium and increase in Lactobacillus , etc ., as well as alleviating gut barrier impairment, inflammatory responses and LPS invasion in the blood circulation. 53 However, there are few reports regarding the role of Seabuckthorn flavonoids in the regulation of the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…[ 79,80 ] Microbiome‐generated compounds, such as protocatechuic acid, urolithins, and phenyl‐γ‐valerolactones share similar antioxidant and anti‐inflammatory properties to the molecules originally contained in food but are also able to promote mitochondrial health and cerebrovascular microcapillary function. [ 81 ] In this context, depending on their absorption, bioavailability, and ability to pass the blood‐brain barrier, secondary metabolites from (poly)phenols may reach the central nervous system and counteract neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%